Handling the Weather : Insurance, Savings, and Credit in West Africa - de Nicola, Francesca (World Bank Group, Washington, DC, 2015)
Farmers in developing countries face a wide array of risks. Yet they often lack formal financial instruments to protect against risks. This paper examines the impact on consumption, investment, and welfare of the separate provision of three financial products: weather insurance, savings, and credit. The paper develops a dynamic stochastic mode to capture the essential features of the lives of West African rural households. The model is calibrated with data from farmers in Burkina Faso and Senegal, to assess quantitatively the effects of three policy interventions. For each intervention the analysis first considers a benchmark scenario that abstracts from the flaws that affect each instrument; later the assumptions are relaxed. Weather insurance offers the largest welfare gains at each level of wealth, although the gains are significantly reduced by introducing a multiple on the insurance premium. Over time, however, savings can lead to substantial gains, higher than those achievable by unsubsidized weather insurance.